Pesticide Labeling: Labeling Claims - Frederick M. Fishel (EDIS, 2019)
This document describes the three basic types of claims made on pesticide labels—1) general claims; 2) claims associated with the product name, and 3) efficacy-related claims. Examples of typical claims are provided as well as claims which may mislead the user of the product. This document is PI-105, one of a series of the Agronomy Department, UF/IFAS Extension. Original publication date February 2006.